Bioassay-guided isolation of anti-hepatitis B virus flavonoid myricetin-3-O-rhamnoside along with quercetin from Guiera senegalensis leaves - Mohammad K. Parvez; Mohammed S. Al-Dosari; Ahmed H. Arbab; Adnan J. Al-Rehaily; Mazin A.S. Abdelwahid (Elsevier, 2020)
Recently, we have shown in vitro anti-hepatitis B virus (HBV) activity of G. senegalensis J.F. Gmel leaves, and Identified quercetin and other flavonoids by HPTLC. Here we report bioassay-directed fractionation of G. senegalensis leaves using column chromatography and isolation of two flavonoinds from the n-butanol fraction, their structure determination (1H NMR, 13C NMR and 2D-NMR) and assessment of antiviral activities (HBsAg and HBeAg assay) in HBV-reporter HepG2.2.2.15 cells. Further molecular docking was performed against HBV polymerase (Pol/RT) and capsid (Core) proteins as well as host-receptor sodium taurocholate co-transporting polypeptide (NTCP). The two isolated bioactive compounds were identified as quercetin and myricetin-3-O-rhamnoside. Quercetin significantly inhibited synthesis of HBsAg and HBeAg by about 60% and 62%, respectively as compared to myricetin-3-O-rhamnoside by 44% and 35%, respectively. Molecular docking of the two anti-HBV flavonoids revealed their higher binding affinities towards Pol/RT than Core and NTCP. In conclusion, this is the first report on anti-HBV active myricetin-3-O-rhamnoside along with quercetin isolated from G. senegalensis leaves. Their possible mode of anti-HBV activities are suggested through binding with viral Pol/RT and Core as well as host NTCP proteins.